The Role of "Green Structures" in Reducing the Environmental Footprint of Urbocenoses - Tkachenko, Tetiana; Voloshkina, Olena; ., .; ., . (International Journal of Engineering and Technology, 2018)
The modern problem of urbocenoses is associated with an increase of the environmental footprint, the main indicator of which is the concentration of CO2 in the atmosphere. One of the ways to reduce carbon emissions is to increase biomass through the Â«green structuresÂ». Nowadays, there are insufficient methods for calculating the accumulation of biomass and sequestration of CO2. As a result, new methodological approaches are proposed.Â Â Â